Jeux de rôle et réconciliation avec les peuples autochtones - Eva Lemaire
In this paper, we propose a reflection on role-playing as a classroom practice inspired by intercultural education but revisited in light of Indigenous perspectives and pedagogies, in the particular context of the reconciliation with First Nations, Métis and Inuit Peoples. This research, based on a practitioner-researcher approach, is mainly based on a data collection driven from 45 students completing their bachelor of Education. The article discusses the value of a holistic pedagogical approach, convening reason, but also emotion, body and spirituality that helps deconstruct and rebuild students'representations of indigenous cultures, inviting future teachers to situate themselves as agents of change in the face of a societal model in crisis.